PERSEPSI GURU DAN SISWA TENTANG FUNGSI UKS (UNIT KESEHATAN SEKOLAH) DI SEKOLAH DASAR MUHAMAMDIYAH 4 SAMARINDA - Faried Rahman Hidayat (Jurnal Ilmu Kesehatan, 2017)
Background : UKS (school health units) are the activities schools that do not can be separated in the life of another at an school, good for students of teachers and the tens of thousands of workers in that school and nowhere. Program on guidance and development office in school a unit of education beyond school implemented through three programs basic (TRIAS UKS) that includes: education health, health services, and provide guidance on the formulation of a healthy school environment the life. Primary school muhammadiyah 4 samarinda own have office but based on the results of an interview from a few teachers and students obtained an less about function UKS.Research objective : this study did to know “perception teachers and students about the function UKS in primary school muhammadiyah 4 samarinda”.Research design : Design this research is descriptive cross sectional. This research used a quantitative approach that is descriptive who gives perception teachers and students to function UKS. Population in this research is primary school teachers from 40 people who taken use total of sampling and students the 3, 4 and 5 class as many as 412 students from 80 people who in extract use random sampling, where this research use of inclusion of criteria and exclusion.Research results : Based on the research done or as many as 72.5% teachers have of knowledge of good, 20% at that time teachers have knowledge enough and as many as 7.75% teachers have lacking knowledge about the function of UKS. The results of the study obtained as many as 52.5% teachers have good attitude and a 47,5% teachers have attitude less than good on the functions UKS. The research found as many as 20% students having knowledge of good, as many as 50% students know enough and as many as 30 % students know less about the function of UKS. The results of the study obtained as many as 57,5 percent of students having good behavior and a 42,5 percent of students having attitude less than good on the functions UKS. Conclusion : Researchers formulate respondents who have knowledge and attitude the majority better because socialization officers office from the Service center for the community on teachers and students has been running cooperative this also happened to activities office in primary schools muhammadiyah 4 samarinda.